Experimental legal regimes (regulatory sandboxes): RUSSIAN AND FOREIGN PRACTICES (Revista de Investigaciones Universidad del Quindío, 2022)
This article provides a comparative analysis of regulatory sandbox implementation in the Russian Federation and foreign countries. Based on the information provided by financial regulators of Bulgaria, Hungary, Georgia, Lithuania, Kyrgyzstan, and Estonia, as wellas on Russian and foreign legislation concerning regulatory sandboxes, the comparative legal study has explored the terminology, legal regulation, and potential application of experimental regimes. This research has analyzed the criteria for proposals related tospecial legal regimes, as well as authorities that regulate the participants of experimental legal regimes and evaluate the results. Testing stages have been specified and a general model of regulatory sandbox development has been provided. The study gives examples of legal experiment practices in the Russian Federation and foreign countries.
Keywords: legal experiment practices; sandbox implementation; financial regulators; legal regimes; legal regulation